Cálculo del Índice de Salud de los Transformadores de Potencia de hasta 69 kV mediante lógica difusa - Peralta Córdova, Jorge Isaac (2022)
The following study looks for propose a fuzzy logic analysis methodology that allows evaluating the health index (HI) of oil immersed power transformers (TP) rated of up to 69 kV, using common variables obtained from power transformer insulating oil diagnostic tests. To define the fuzzy inference system (FIS), previously validated studies are taken as a reference, added to expert criteria and IEEE regulations related to power transformer mineral oil quality. In this way, the fuzzy rules and the membership functions for each input and output variable are defined, then the system is modeled into a specialized use software to optimize calculation procedure. A comparative evaluation is carried out between the proposed model calculated health index and those obtained through reference study. Results show a high coincidence in terms of linguistic assessment. Once the model has been validated, the diagnostic test results carried out on a fleet of 10 power transformers belonging to a domestic distribution company, are taken to determine the HI of each unit. The evaluation results show that 9 out of 10 units are in a health status at least “good”, so, specific maintenance tasks are not required. Keywords: Power transformer, health index, fuzzy logic, dielectric oil.